The New global political economy : from crisis to supranational integration - Fiorentini, Riccardo (Edward Elgar Publishing Ltd. CheltenhamGB, 2012)
Analysises the causes of the 2008 financial crisis and the measures of political economy required to build a safer and mor stable international order.